Sustaining optimal performance when the stakes could not be higher: Emotional awareness and resilience in emergency service personnel (with learnings for elite sport) - Jacobs, Emily; Keegan, Richard J. (Frontiers in Psychology, 2022)
Emergency services personnel are a high stress occupation, being frequently confronted with highly consequential stressors and expected to perform: without fault; under high pressure; and in unpredictable circumstances. Research often invokes similarities between the experiences of emergency services personnel and elite athletes, opening up the possibility of transferring learnings between these contexts. Both roles involve genuine risks to emotional wellbeing because their occupations involve significant stress. Similarly, both roles face obstacles and injury, and their ‘success’ is dependent on high-quality execution of their skills under pressure. As such, both occupations are required to have resilience and effective coping abilities to ensure psychological well-being. Researchers suggest emotional awareness may be a key variable in the management and maintenance of resilience. This study: (1) explored the experiences of emergency services personnel; (2) characterised connections between emotional awareness and resilience; and (3) reflected on the ways these findings can be extrapolated to elite athletes. We analysed eleven interviews with emergency services personnel. Participants identified resilience as crucial when coping with stress, however, many defined resilience as remaining unaffected by stress rather than, for example, managing and responding to it. Participants defined emotional awareness as understanding their emotions, and they recognised associated benefits for coping, resilience and burnout. Nevertheless, most participants did not engage in practices to improve their emotional awareness. Barriers, such as maladaptive beliefs and help-seeking stigma, interfered with participants’ ability to cultivate emotional awareness, to promote resilience. In contrast, some participants described profound improvements in resilience and coping following the cultivation of emotional awareness. This finding illustrates that systemic change must target the individual, team, and organisation to correct misperceptions about resilience, emotional awareness, and psychological help-seeking. Developing emotional awareness may help emergency services personnel and other high stress occupations like elite athletes process difficult experiences and enhance their resilience, promoting well-being and career longevity.